How Gender Changed the History of Medicine - Morantz-Sanchez, Regina (My University, 2007)
Laupus Library History Collections & the Department of Bioethics & Interdisciplinary Studies sponsor the History of Medicine Presentations as an educational service for the East Carolina University community. The Library hopes that the speakers and topics selected will promote a greater understanding of the historical and philosophical underpinnings of today's health care disciplines.
Lecture associated with "Changing the Face of Medicine: Celebrating America's Women Physicians" traveling exhibition
Keywords: Medical History Interest Group; MHIG; Physicians, Women--history; Women; History of Medicine